LabView – Arduino System for Determining the Vibration of Stepper Motors - ȚEPELEA Laviniu; TOMȘE Marin Titus (Journal of Electrical and Electronics Engineering, 2022)
Brushless stepper motors are increasingly used in many applications. Their control can be done using specialized drivers that offers several control modes. Engine performance depends on the type of driver used. In order to study the influence of the driver on the vibrations that occur in the operation of stepper motors, an application was designed using LabView together with Arduino. The VI used allows stepper motor control and vibrations measurement with the help of an analog acceleration sensor.